KEBANGKITAN PERADABAN ISLAM PADA ABAD KLASIK - A Syamruddin Nasution (Sosial Budaya, 2015)
This article reviewing the history of islamic civilization has experienced a resurrection in the classical century, especially in the three daulah, namely Daulay Abbasiyah in Baghdad, Daulay Umayyah in Cordova and Daulay Fatimiyah in Mesir. Islamic civilization and science at the time it had been developed and the resurrection very rapidly once. The three daulah vied to advance the Islamic civilization, science and literateur in their respective areas. What efforts which is conducted Daulah Abbasiyah make Baghdad as an intellectual city which is visited by scientists, litterateur to stand Nizamiyah University. Alsowhat is done Daulah Umayyah Spanyol for the resurrection ofIslamic civilization so that in each city there is University, among others, University ofCordova, University ofGranada, University ofSvilla and etc. Similarly what is taken daulah Fatimiyah in Mesir to the rise Islamic civilization to the founding of the University of al-Azhar, all of which are discussed in this article. This studyusesthe methodof analysisdescription There are three daulah mentioned above to discover the cause of their resurrection. Withstudying the development and resurrection of Islamic civilization, science and litterateur three Daulah can be used as guidelines in an effort to resurrection the civilization and science in Indonesia today.Syamruddin Nasution